Mengatasi Kesenjagan Digital dalam Pendidikan: Sosial dan Bets Practices - Adha Zam Zam Hariro; Novia Rahmadani Harahap; Putri Puspitasari; Fenika Ardiyani; Windi Melisa; Juliani Juliani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The digital divide is a gap in the field of Information and Communication Technology for both individuals and certain groups. The research method used in this research is a qualitative research method with literature study. The research results show that in the current digital era, educational tools also create gaps in education. Several factors that influence the digital divide are socio-demographic factors, digital literacy factors, and needs factors. Some solutions that can be taken include improving internet infrastructure and digital technology in remote and rural areas, increasing teachers' ability to use technology for learning, and increasing access. students to quality digital educational content.